Aquisição do controle postural em lactentes nascidos a termo pequenos para idade gestacional no 12° mes de vida - Ana Carolina Gama e Silva Brianeze (2006)
significantly lower than the AGA group.Maternal occupation was 0.22 times more associated to the SGA group.The motor index score was significantly lower in the SGA group (p= 0.046).In the study of the postural control of the sample, there was significant difference between the groups in the item MO 61: stands up alone (p= 0.019) and MO 71: walks sideways (p= 0.020), with lower frequency for the SGA Abstract xxxix group.It was concluded that infants born SGA showed significantly lower score in the motor scale, and the items stands up alone and walks sideways showed significantly lower frequency for the SGA group.